2016
DOI: 10.1016/j.agee.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combined application of organic amendments and fertilizers on crop yield and soil organic matter: An integrated analysis of long-term experiments

Abstract: A comprehensive synthesis of 32 long-term experiments in China is performed by comparing yields and SOM contents and their time by nutrient management responses (TNMR) to determine whether and to what extent combined application of organics amendments and fertilizers (organics+fertilizers) can increase productivity and soil organic matter (SOM) content and enhance the sustainability of diverse cropping systems. TNMR is defined as percentage changes over time in yields and SOM contents in external nutrient inpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
102
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(118 citation statements)
references
References 34 publications
14
102
0
2
Order By: Relevance
“…Among all the nutrients, soil organic carbon (SOC) is an important indicator, which provides plant nutrients, increases soil aggregation and also plays an important role in soil water conservation and soil biological activity (Rajan, Natarajan, Kumar, Badrinath, & Gowda, 2010;Wiesmeier et al, 2019). The SOC content can be directly affected by mineral fertilizer (Poeplau & Don, 2015;Wei et al, 2016), with some studies claiming that the long-term use of mineral fertilizers leads to a slower decrease in SOC compared with control plots (Wei et al, 2016). Mineral fertilizer also may augment SOC by promoting plant growth and thereby increasing the amount of plant residue and may lead to enhanced loss of SOC by accelerating its rate of oxidation or residue decay and indigenous organic material (Ladha, Reddy, Padre, & van Kessel, 2011).…”
Section: Core Ideasmentioning
confidence: 99%
“…Among all the nutrients, soil organic carbon (SOC) is an important indicator, which provides plant nutrients, increases soil aggregation and also plays an important role in soil water conservation and soil biological activity (Rajan, Natarajan, Kumar, Badrinath, & Gowda, 2010;Wiesmeier et al, 2019). The SOC content can be directly affected by mineral fertilizer (Poeplau & Don, 2015;Wei et al, 2016), with some studies claiming that the long-term use of mineral fertilizers leads to a slower decrease in SOC compared with control plots (Wei et al, 2016). Mineral fertilizer also may augment SOC by promoting plant growth and thereby increasing the amount of plant residue and may lead to enhanced loss of SOC by accelerating its rate of oxidation or residue decay and indigenous organic material (Ladha, Reddy, Padre, & van Kessel, 2011).…”
Section: Core Ideasmentioning
confidence: 99%
“…Although previous research has found a positive effect of either organic inputs or SOM on crop yields (Monreal et al 1997;Wei et al 2016), Oelofse et al (2015) argue that in these studies the effect of nutrients is seldom separated from other effects. In fact, Wei et al (2016) also mention this as the largest limitation of their study.…”
mentioning
confidence: 98%
“…A recent meta-analysis of 32 long-term experiments in China compared the combined use of organic inputs and fertilizers with either only organic inputs or only fertilizers (Wei et al 2016). The average yield increase of combining organics and fertilizers on wheat, maize and rice was found to be 8 % compared to using only fertilizers.…”
mentioning
confidence: 99%
“…Los requerimientos de las plantas de acelga durante el ciclo de cultivo son elevados en nitrógeno y potasio según [14], debido a que la acelga tienealto contenido nutricional en hierro, calcio, potasio, zinc, magnesio, sodio y fosforo. Los tratamientos 3 y 4 que contienen 33 y 50% de B. de oro tienen altos contenidos de estos nutrientes, lo cual ayudo al mejor desarrollo de las plantaslas cuales fueron capaces de aprovechar los abonos orgánicos en función de su rendimiento.…”
Section: Producción De Acelga (Beta Vulgaris)unclassified